2008
DOI: 10.2106/jbjs.f.00739
|View full text |Cite
|
Sign up to set email alerts
|

Unicompartmental Knee Arthroplasty with the Oxford Prosthesis in Patients with Medial Compartment Arthritis

Abstract: With this unicompartmental knee arthroplasty, the mechanical limb alignment resulting from balancing the knee ligaments, accomplished without releasing them, was consistently through the center of the knee. Progression of arthritis in the lateral compartment was the most common reason for late failure in this series and was not related to the initial postoperative alignment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
88
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(96 citation statements)
references
References 8 publications
4
88
1
3
Order By: Relevance
“…Discrepancies have been observed between the survivorship reported in the United Kingdom by the Oxford Group and the survivorship reported in North American patients by independent teams [12,26,39,40], possibly related to the potential differences between the patients in the United Kingdom and in North America [7]. The survivorship reported in the Swedish and the Finnish Joint registry failed to demonstrate any difference between fixed-and mobile-bearing UKA [22-24, 34, 35].…”
Section: Discussionmentioning
confidence: 99%
“…Discrepancies have been observed between the survivorship reported in the United Kingdom by the Oxford Group and the survivorship reported in North American patients by independent teams [12,26,39,40], possibly related to the potential differences between the patients in the United Kingdom and in North America [7]. The survivorship reported in the Swedish and the Finnish Joint registry failed to demonstrate any difference between fixed-and mobile-bearing UKA [22-24, 34, 35].…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective studies suggest the survivorship of UKA, performed for certain indications approaches that of TKA [14,19,34,36]. There are purported advantages of a UKA over a TKA [16,30,39].…”
Section: Discussionmentioning
confidence: 99%
“…Patients who have UKAs generally have shorter hospital stays [7,30,39], and the procedure appears cost-effective when measured in units of quality-adjusted years [38,39]. Some studies of the survivorship of prostheses used in UKA, regardless of type, have reported poor survivorship rates, when compared with prostheses used in TKA [17,23,25], whereas others report 10-and 15-year survivorship rates of 85% to 95% for UKA comparable to those for TKA [14,34,36]. One report suggests the higher reported survival of UKA in some studies relates to patient selection, improved surgical technique, and better prosthetic design [34].…”
Section: Introductionmentioning
confidence: 99%
“…Estudo multicêntrico com 294 próteses de Marmor relatou 91,4% de sobrevida de 10 anos (25) . Estudos recentes, sobretudo a partir de 1996, destacam a importância da técnica cirúrgica apurada e, principalmente, da escolha correta dos pacientes, o que, junto com a melhora da biomecâ-nica dos implantes, são fatores determinantes de melhores resultados e do "renascimento" da UNI (11)(12)(13)(14) .…”
Section: Discussionunclassified
“…Revisão da literatura mais recente demonstra que atualmente a sobrevida da UNI em 10 anos é de 90-93%, o que se assemelha à da artroplastia total do joelho (11)(12)(13)(14) . Essa evolução nos resultados tem sido atribuída à melhor seleção dos pacientes, técnica cirúrgica mais apurada e aperfeiçoa-mento no desenho dos implantes (15) .…”
Section: Introductionunclassified